School Counselors Share Their Favorite Group Activities: A Guide to Choosing, Planning, Conducting, and Processing - Foss, Louisa L.; Association for Specialists in Group Work (Association for Specialists in Group Work, 2008)
Keywords: Educational counseling; Group counseling for children; Group counseling for teenagers; Activity programs in education; dept.csp; faculty_collection

Addressing students' social and emotional needs: the role of mental health teams in schools. - Haynes, Norris M (Journal of health & social policy, 2002)
Children in today's society face many stresses from a variety of sources that have a major impact on thier psychosocial adjustment and academic performance in school. These stressful events and thier consequences on the quality of life and academic success are particularly significant among low-income and ethnic minority students in American society. Many schools have adopted strategies to help students who are impacted by stressful life events to deal affectively with their problems in an attempt to reduce school failure and school dropout rates among these students. Most notable among these strategies are school-based mental health programs including the establishment of school-based mental health teams which seek to proactively address individual student concerns while improving the general climate of schools. The evidence seems to support the claim that these school-based services have a positive impact on students' social and emotional well-being as well as on their academic achievements. However, with more careful monitoring and much more consistent support from administrators and policy makers, these school-based approaches can more fully realize their potential to enhance the quality of life and to positively impact the future of many poor and ethnic minority students.
33 citations (Crossref) [2023-10-31] Place: United States Haynes, Norris M. Center for Community and School Action Research, Southern Connecticut State University, USA.
Keywords: *Mental Health Services/og [Organization & Administration]; *Patient Care Team; *School Health Services/og [Organization & Administration]; *Social Support; *Stress; Psychological/th [Therapy]; Adolescent; Child; Children's mental health; Female; Humans; Male; Minority mental health; School-based mental health; Social Problems; Social Work; Psychiatric; Social and emotional learning; Socialization; Student health; Teaching/mt [Methods]; United States; academic achievement; child; child care; dept.csp; emotional stability; ethnic group; health care need; human; life event; lowest income group; mental health; mental health service; policy; quality of life; review; school health service; social learning; social policy; social psychology; student; wellbeing

An exploration of themes that influence the counselor education doctoral student experience. - Protivnak, Jake J; Foss, Louisa L (Counselor Education and Supervision, 2009)
The purpose of the present study was to explore the themes that counselor education doctoral students perceive as influencing their experience. The results of an exploratory qualitative study in which counselor education doctoral students provided their perceptions of what helped or hindered their progress are presented. Themes identified as both positively and negatively influencing their experiences were departmental culture, mentoring, academics, support systems, and personal issues. Recommendations are provided for counselor educators to consider in their work with doctoral students. © 2009 by the American Counseling Association. All rights reserved.
48 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/141-404-873-290-857 tex.type: [object Object]
Keywords: dept.csp

Social competence, social support, and academic achievement in minority, Low-Income, urban elementary school children - Elias, Maurice J; Haynes, Norris M (School Psychology Quarterly, 2008)
Despite living in disadvantaged urban communities experiencing social and economic hardships, many children emerge with positive outcomes. Social-emotional competence and social support were hypothesized to have strong influences on academic trajectories during the critical period of academic skill acquisition. Participants were 282 third-grade students from six elementary schools in a Northwestern urban community. Beyond the importance of prior levels of academic competence, considerable variance in end-of-year academic outcomes was predicted by initial levels of academic social-emotional competence and improvements in social-emotional competence and perceived teacher support over the course of the year. Noteworthy is that findings were strongest for African-American students, but methodological caveats regarding research with underachieving minority youth were discussed. The findings suggest that school psychologists and others designing interventions to improve achievement of disadvantaged students should address social-emotional competencies and classroom climate, especially teacher support of students.
170 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/046-548-958-283-276 tex.type: [object Object]
Keywords: academic underachievement; dept.csp; prevention; resilience; social-emotional competence; urban minority youth